MERCANTILSM OF KNOWLEDGE IN EDUCATION: A CASE STUDY AT MELATI SUKMA ELEMENTARY SCHOOL DENPASAR - Suda, I Ketut; Bawa Atmaja, I Nengah; Ardika, I Wayan; Parimartha, I Gde (E-Journal of Cultural Studies; Vol. 4, No. 1 Januari 2010, 2012)
This study discusses”Mercantilism of Knowledge in Education: a Case Study atMelati Sukma Elementary School Denpasar”. The matter observed is a shift ofeducational paradigm, from enlightenment paradigm into instrumental paradigm. Whenthe system of market economy influenced the Indonesian economic system in 1960s or inthe beginning of 1970s, which is now getting more materialistic-capitalistic, socialorganizations such as educational organizations (read: schools) have found it difficult toavoid it. This study aims at exploring why the management of Melati Sukma ElementarySchool Denpasar has implemented “mercantilism of knowledge” in education, and whythe consumers have accepted it. This study also aims at identifying the mechanism ofhow “mercantilism of knowledge” has occurred at Melati Sukma Elementary SchoolDenpasar, and its implications on the pupils, the school, the learning-teaching process,and on the community.Qualitative method was employed for conducting the research. In this context,various types of information related to why the school management has implemented themercantilism of knowledge, the mechanism of how it has occurred, and its implicationson the pupils, the school, the process of learning and teaching process in the classrooms,and the community were obtained. Firstly, problems were identified, then theories forexamining the data were selected, later the primary and secondary data were collected,next the selected data were analyzed and interpreted. Finally, the report writing and theresults of the research were constructed. The theories employed are Comodificationtheory, Hegemony theory, and Deconstruction theory.The results are as follows: firstly, those which have been responsible for themercantilism of knowledge are the fact that the teachers have been getting marginalizedfrom the process of national development, the system of market economy and theconsumptive attitude of the community including the teachers have been getting stronger.The parents’ motivation to send their children to that school has also been in included inthe first result. Secondly, the mercantilism of knowledge at Melati Sukma ElementarySchool has also been implemented through the domination, hegemony, and power of theschool management over the pupils’ parents in the forms of sales of various industrialproducts, provision for additional lessons, and other types of payments. Thirdly, themercantilism of knowledge has also resulted from the attempts made by the school management to make the school look more glorious. The learning process has not beenoriented towards the attempts made to increase the pupils’ intelligence but towards theeconomic advantages. Where the parents will send their children does not depend on thequality of education but on the prestige instead.
Keywords: mercantilism of knowledge, education, system of market economy, marginalization of teachers in the developmental process